The boy who saw - Toyne, Simon, 1968- (Toyne, Simon, 1968- Solomon Creed series., 2017)
"Solomon Creed, the enigmatic hero introduced in The Searcher, must stop a killer tied to a conspiracy stretching back over generations to the dying days of World War II. Solomon Creed has no recollection of who he is, or where he comes from. The only solid clue to his identity is a label stitched in his jacket that reads: "This suit was made to treasure for Mr. Solomon Creed." The jacket fits perfectly, and so does the name, but there is a second name on the label, the name of the tailor who made the suit and an address in southern France. Solomon heads to France in search of this man, hoping to discover more about who he is. But instead of answers he finds a bloody corpse, the Star of David carved into his chest and the words "Finishing what was begun"daubed in blood on the wall. When the police discover Solomon at the crime scene they suspect he is the murderer and lock him up. Solomon must escape to clear his name and solve the mystery of why the last remaining survivors of a notorious Nazi death camp are being hunted down and murdered. Only by saving these survivors from evil can Solomon hope to piece together the truth about a decades-old conspiracy as well as discover the key to his own identity"--